The law 10.639 and the cultural diversity in the "Lauro Muller" State School - Isadora Marques Crochik (Universidade Federal de Santa Catarina, 2008)
This text is the report of an exploratory work, without pretension scientific, held together with children of the College Lauro Muller. My objective was to accomplish a first contact with the children, looking for a picture in your way of thinking on the slavery, your origins and consequences. I was not in charge of in to analyze and to interpret the children's speeches, because my larger interest in this text is not to discuss what they think, nor to relate your thought with the thought and adults' attitude. This work is, actually, a base to think efficient ways to include discussions and relative anthropological concepts to the cultural diversity and the subject of the blacks in Brazil in the daily of the school.